what is -a^-2 if a =-5?

1 answer

To find the value of -a^-2 when a = -5, we substitute -5 for 'a' in the expression:

-a^-2 = -( -5 )^-2

Now, we simplify the expression inside the parentheses first:

-( -5 )^-2 = -( -1/5 )^-2

To simplify further, we apply the negative exponent:

-( -1/5 )^-2 = -(-5/1)^2

Now, we square the numerator and denominator:

-(-5/1)^2 = -(25/1)

Finally, we simplify the expression by multiplying -1 with 25:

-(25/1) = -25

Therefore, -a^-2, when a = -5, is equal to -25.